OPINI AUDIT GOING CONCERN: KAJIAN BERDASARKAN LEVERAGE, KOMISARIS INDEPENDEN, MODEL PREDIKSI KEBANGKRUTAN, DAN OPINI AUDIT TAHUN SEBELUMNYA - Juliawan, Hardi; Yendrawati, Reni (Faculty of Economics and Business, 2024)
This study aims to analyze the factors that influence going concern audit acceptance. The independent variables used in this study are independent commissioners, leverage, bankruptcy prediction models, and previous year's audit opinion, while the dependent variable is the acceptance of going-concern audit opinions. The population in this study are manufacturing companies in the consumer goods industry sub-sector listed on the Indonesia Stock Exchange in 2016-2020. This research is quantitative by using purposive sampling method to determine the sample used in the author's research. Based on the purposive sampling method that has been used, the samples obtained were 38 companies. The analytical method used to test the effect of the independent variable on the dependent variable is logistic regression. The results of this study show that the independent variables of the bankruptcy prediction model have a negative effect on the acceptance of going-concern audit opinions and the previous year's audit opinions have a positive effect on the acceptance of going-concern audit opinions, while the independent variables of independent commissioners and leverage do not affect the acceptance of going-concern audit opinions